Konfigurasi Nalar TafsÃ„Â«r al-MaqÃ„ÂÃ¡Â¹Â£idÃ„Â«: Pendekatan Sistem Interpretasi - Wathani, Syamsul (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
This article discusses the concept of maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«ÃŠÂ»ah (the goal of sharia) as a basis of the interpretation of the Qur'an. The points to be discussed are focused on two lines, namely the paradigm of tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â« (the goal interpretation) and the configuration of the reason of tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â«. The approach used is the hermeneutic approach within the framework of the structure of the interpretation system. It is by using the approach and the analysis, this article draws conclusions to the three lines of the understanding on the tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â«: (1) The paradigm of tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â« is the perspective toward the Qur'an and its interpretation along with the concept of maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«ÃŠÂ»ah as the starting point, working with the emphasis on the harmonization between the text and the spirit of justice as has been conceptualized in the theory of maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«ÃŠÂ»ah. Thus, tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â« emphasizes logical reasoning for the public benefit to be more powerful than the text reasoning. (2) Hermeneutical reasoning of tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â« is supported by three pillars of awareness: the historical, theoretical, and practical awareness. The three pillars are then actualized in the step of interpretation covering: contextualization, decontextualization, and ends with a re-contextualization. (3) As a system of interpretation, tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â« passes the way of interpretation through the rules of linguistic, the analysis of hermeneutics and the analysis of public benefit (maÃ¡Â¹Â£laÃ¡Â¸Â¥ah). Keywords MaqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«ÃŠÂ»ah, hermeneutics, interpretation system, tafsÃ„Â«r al-maqÃ„ÂÃ¡Â¹Â£idÃ„Â«.